Multibiomarker toxicity characterization of uranium mine drainages to the fish Carassius auratus - Bessa, M. L. (2022)
The release of acidic effluents, naturally enriched in metals and radionuclides, is the main legacy of uranium mines. Generally, metals dissolved by these acidic effluents can cause significant alterations in exposed organisms, with distinct toxicological outcomes. In this study, 72 individuals of the freshwater fish species Carassius auratus were exposed in situ for different periods (8, 16, 24, and 48 h) to water from a pond (treatment pond (TP)) with a chemically treated effluent and a reference pond (PRP), in the vicinity of the Cunha Baixa uranium mine (Portugal). Comparing the water of the two ponds, the PRP pond was characterized by higher pH and oxygen values and lower conductivity and hardness values. Regarding total metal concentrations, among others, magnesium (56,000 μg/L), sodium (17,400 μg/L), zinc (86 μg/L), manganese (6340 μg/L), and uranium (1380 μg/L) concentrations in the TP pond were above the values obtained for the PRP pond. The values of manganese and uranium exceeded the values of quality criteria established for surface waters for cyprinids and for irrigation purposes. After exposure to pond water, significant differences were recorded for several biomarkers: (i) between ponds for acetylcholinesterase (AChE) with higher activities for animals from the PRP and glutathione-S-transferase (GST) activities that were particularly enhanced in animals from the TP pond; (ii) between ponds and exposure periods for lactate dehydrogenase (LDH) activity, since organisms from PRP pond presented always higher values than those from the TP pond, and among these, organisms exposed for the longer period presented a further depression in LDH activity; and (iii) between exposure periods for erythrocyte micronucleus. GSTs and LDH were the most sensitive biomarkers within the timeframe of the in situ assay performed. Despite the alleged efficacy of the chemical treatment (evidenced by a significantly lower pH), some metals persisted in the treated effluent (TP pond), potentially contributing to the induction of oxidative stress or increased conjugation metabolic activity in fish.